Drivers and deterrents of child sexual offending: analysis of offender interactions on the darknet - Wolbers, Heather (Trends & issues in crime and criminal justice, 2024)
This study examined 17 threads on a darknet forum for undetected online and contact child sexual offenders (CSOs) to identify key drivers and deterrents of offending and to inform intervention approaches. CSOs on the forum normalised sexual contact with children while minimising or denying the resulting harm and shifting the responsibility for offending. These cognitive drivers of offending were coupled with access to technology and close engagement with online communities supportive of child sexual abuse. Acknowledgement of the harm to children, feelings of guilt and shame, and concern about being caught by law enforcement or detected by family and friends acted as deterrents to continued offending.